As vozes do progresso: os liberais positivistas na imprensa capixaba oitocentista (Ágora Journal, 2020)
This article aims to analyze the performance of the Group Liberal Positivist through the newspapers of Espírito Santo in the context of the crisis of the Brazilian Empire. From the analysis of the writers and intellectuals adept at positivism in the province we highlight the main ideas of the group. Through the methodology of political languages, this study highlights the concepts most used by positivists, as well as the diffusion of liberal political ideas within the period of crisis of the Empire.